Propuesta de mejoramiento en la calidad de la empresa Cultiflores y Comercializadora Agrícola Sarinah S.A.S (2020)
The main objective of this document is the proposal to improve the quality of the company Cultiflores y Comercializadora Agrícola Sarinah S.A.S., a company in the floriculture sector dedicated to the production and commercialization of cut flowers for export. Initially, a diagnosis of the current state of the company is carried out against compliance with the requirements of the NTC ISO 9001: 2015 standard, and the complaints, claims and returns of the last semester are analyzed. Subsequently, the main causes of the unwanted effects are identified, and based on the results obtained, an action plan is established with the purpose of improving product quality and customer satisfaction based on the structure of the PDCA cycle.